Rediscovery and redescription of Leodice laurillardi (Quatrefages, 1866) comb. nov. (Annelida: Eunicidae)—a rare European polychaete or just an overlooked species? - Arias, Andrés; Fernández-Álvarez, Fernando Á.; Martins, Roberto; Anadón, Nuria (Zootaxa, 2015)
The eunicid polychaete, Eunice laurillardi Quatrefages, 1866, originally described from the central Mediterranean, has been discovered on the northern Iberian Peninsula, constituting the first report of the species since its original description. The new specimens are compared with the type collection and the species is redescribed. Furthermore, the species is assigned to the genus Leodice Savigny in Lamarck, 1818, based on information provided by re-examination of type material and the newly collected specimens. A summary of the complex taxonomic history of the species and a discussion of its current status are also provided.